IDE BUNUH DIRI PADA MAHASISWA YANG KESEPIAN: A LITERATURE REVIEW - Kusdemawati, Jeny; Sa’adah, Nurus (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Recently, there has been a rash of suicides committed by students. Suicide initially arises because of suicidal ideation. This cause of suicidal ideation is the feeling of loneliness. This feeling arises, among other things because the family does not function. Families that should be able to perform their function, however, intead seem to give distance to children. Communication is one of the important things so that cildren do not feel lonely een though they are overseas. This study uses literature review type of research, the result of this study is that family plays an important role in as a form of defense for adolescents as a prevention of suicidal ideation that’s leads to suicide.